Strategi Pembelajaran Berbasis Al-Qur’an sebagai Landasan Pendidikan Karakter - Rosmiati Ramli; Muh. Iqbal Muhidin; Yenni, Yenni; Rosiana Syahbaniar; Rudi Hartono (FKIP UNSULTRA, 2026)
Character education is an important foundation in shaping students with noble character, responsibility, and integrity. In the context of Islamic education, the Qur'an plays a central role as a source of values, norms, and relevant life guidelines that can be used as a basis for character learning strategies. This article aims to systematically review various research findings related to Qur'an-based learning strategies as a foundation for character education. The method used is a literature study by reviewing national and international journal articles, scientific books, and relevant academic sources from the past ten years. The results of the study indicate that the integration of Qur'anic values ​​​​in learning can strengthen students' religious character, honesty, discipline, responsibility, and empathy. Effective strategies include teacher role models, habituation based on Qur'anic verses, contextual learning, reflection on values, and integration of the Qur'an in all subjects. Qur'an-based learning functions not only as a transmission of knowledge, but also as a means of internalizing values ​​​​and forming attitudes. Thus, Qur'an-based learning strategies can be a comprehensive approach to strengthening character education in schools. This article is expected to serve as a conceptual reference for educators in designing learning oriented toward holistic character development of students.